The influence of nocturnal use of complete dentures on cardiorespiratory parameters of patients with obstructive sleep apnea: a systematic review and meta-analysis - Nova, Taciana Emília Leite Vila; Gomes, Jéssica Marcela de Luna [UNESP]; Vasconcelos, Belmiro Cavalcanti do Egito; Pellizzer, Eduardo Piza [UNESP]; Moraes, Sandra Lúcia Dantas (Springer Nature, 2022)
Objective: To assess whether wearing complete dentures during sleep influences the cardiorespiratory parameters of patients with obstructive sleep apnea (OSA). Materials and methods: A systematic review was performed based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines to determine whether wearing complete dentures during sleep influences the cardiorespiratory parameters of patients with OSA. An electronic search was performed in four databases, PubMed/MEDLINE, Cochrane Library, Web of Science, and SCOPUS, and in the gray literature (TRIALS) until November 2021. This review included clinical trials, randomized clinical trials, and studies in which patients using conventional complete dentures were diagnosed with OSA using polysomnography and the cardiorespiratory parameters were measured using oximetry or polysomnography during sleep. Results: In total, 788 references were found in the database, and 12 articles were selected for full reading. Six articles were selected for qualitative and quantitative analyses after applying the inclusion and exclusion criteria and reading the full article. The meta-analysis showed that mean oxygen saturation (SpO2) increased with the use of complete dentures (p = 0.001), but the other parameters showed no significant differences between those wearing and not wearing dentures during sleep. Conclusions: The mean SpO2 reduced in patients wearing complete dentures, but the other cardiorespiratory parameters evaluated were not affected. Clinical relevance: This study indicates a possible influence of the use of complete dentures on the mean SpO2 during sleep. The use of complete denture could aid other treatments in improving respiratory and sleep quality.
Keywords: Cardiorespiratory; Edentulism; Obstructive sleep apnea; Sleep